Moved by Social Justice: The Role of Kama Muta in Collective Action Toward Racial Equality - Lizarazo Pereira, Diana M.; Schubert, Thomas W.; Roth, Jenny (Frontiers in Psychology, 2022)
Participation in collective action is known to be driven by two appraisals of a social situation: Beliefs that the situation is unfair (injustice appraisal) and beliefs that a group can change the situation (collective efficacy appraisal). Anger has been repeatedly found to mediate the relationship between injustice appraisals and collective action. Recent work suggests that the emotion of being moved mediates the relationship between efficacy appraisals and collective action. Building on this prior work, the present research applies kama muta theory to further investigate the relationship between efficacy appraisals and collective action. Kama muta is a positive emotion that is evoked by a sudden intensification of communal sharing, and largely overlaps with the English concept being moved. We investigated its relationship with collective action in both advantaged and disadvantaged racial groups in the context of the Black Lives Matter Movement (BLM) in Spring of 2020. In one pilot study (N = 78) and one main study (N = 215), we confirmed that anger toward the system of racial inequalities mediated between injustice and collective action intentions, and that kama muta toward the movement mediated between collective efficacy and collective action intentions. Both mediations were found for both Black and White participants. We also observed additional unpredicted paths from anger to kama muta and from efficacy to anger. Together, this provides evidence for the pivotal role of emotions in collective action intentions, but also points out that appraisals need to be better understood.